A hydrazine-based thiocarbamide probe for colorimetric and turn-on fluorometric detection of PO43− and AsO33− in semi-aqueous medium. (26th March 2018) - Purkait, Rakesh; Maity, Suvendu; Sinha, Chittaranjan
Abstract : 20% of the population in West Bengal, India is at risk to fatal levels of arsenic. Easy detection of As(iii ) is demonstrated by the naked eye using a hydrazine-based thiocarbamide reagent. Limit of detection is 15 nM (AsO3 3− ) at pH 8–12. Abstract : 2, 6-Bis( N -ethylhydrazonethiocarbamide)-4-methyl-phenol (HTP ) recognizes PO4 3− and AsO3 3− and is effective as a colorimetric and turn-on fluoremetric sensor in the presence of a large number of biologically important cations and anions. The limit of detection (LOD) is 34 nM for PO4 3− and 15 nM for AsO3 3− . The composition of the probe–anion association has been established by Job's plot, 1 H-NMR titration and HR-MS data. The Density Functional Theory (DFT) computation technique is used to optimize the structure that has been compared with an X-ray structure ofHTP and the calculated electronic properties are correlated with the experimental results. Turn-on detection of PO4 3− and AsO3 3− is also successfully utilized for the fabrication of an 'OR' gate. The probe, HTP, is used for analysis of the ground water of Jadavpur, Kolkata.